Distress and psychological morbidity do not reduce over time in carers of patients with high-grade glioma - Halkett, Georgia; Lobb, E.; Shaw, T.; Sinclair, M.; Miller, L.; Hovey, E.; Nowak, A. (Springer, 2016)
Purpose: This study aimed to determine how carer distress and psychological morbidity change over time following a patient’s diagnosis of high-grade glioma (HGG) and identify factors associated with changes in carers’ psychological status. Methods: Carers of patients with HGG planned for chemoradiotherapy were recruited to this longitudinal cohort study. Carers completed questionnaires during patients’ chemoradiotherapy and 3 and 6 months later including the following: the Distress Thermometer (DT); General Health Questionnaire-12 (GHQ-12); and three single-item questions about understanding of information presented by health professionals, confidence to care and preparedness to care for their relative/friend. Linear latent growth models were applied. Results: The time 1 questionnaire was completed by 118 carers, of these 70 carers provided responses to the third time point. Carer distress and psychological morbidity were most prominent proximal to diagnosis, but remained high over time. Sixty-two percent of participants had moderate or high distress on the DT at time 1, 61% at time 2 and 58% at time 3. Scores on the DT and the GHQ-12 correlated significantly at all time points as did changes in scores over time (p < .001). However, for individual carers, the DT or GHQ-12 scores at one time point did not strongly predict scores at subsequent time points. Conclusion: In carers of patients with HGG, distress levels are consistently high and cannot be predicted at any time point. Carers should be monitored over time to identify evolving psychological morbidity. The single-item DT correlates highly with GHQ-12 scores and is a suitable tool for rapid repeated screening.